The Influence of Hybridity on Salwa's Marriage in the novel Once in a Promised Land - Nadhira Harly; Gina Adisty Maharani (Litteratura: Jurnal Bahasa dan Sastra, 2023)
Hybridity, or the practice of blending cultures as diasporic individuals engage with locals in the country they moved to, can have a significant impact on an individual's life, such as on their relationship with their partner. This paper discusses the ways in which hybridity shapes the marriage life of the protagonist in the 2008 novel Once in a Promised Land by Laila Halaby. The study used a qualitative descriptive approach and Homi Bhabha's hybridity theories to analyze the novel's portrayal of the Jordanian married couples' conflicting pursuit of the American Dream, which gets complicated as more people get involved. The protagonist, Salwa, who has a hybrid identity that combines elements of their ancestral culture with the culture of the country in which they live, faces challenges with the hybridity of both her and her partner, Jassim, that affect their marriage. These challenges stem from the clash between Salwa's hybrid belief—the traditional Jordanian value of believing that someone can not be a complete woman until she bears a child that gets assimilated into her vision of a free-willed American woman—and Jassim's own vision of the American Dream as the traditional leading figure who gets control over their family, which does not believe that having a child is a form of freedom. During this conflict, a man named Jake comes into Salwa's life and gives her a false hope of a "free and welcoming home" in him, making her cheat on Jassim despite her own Eastern values echoing inside her mind. The novel highlights how hybridity can create tension and complexity within a marriage as Salwa and Jassim navigate their cultural differences while striving to live peacefully in their "home." The research deduced that Salwa and Jassim's clash, along with the involvement of Jake in their marriage, is due to their inability to adjust to the hybridity of their identities and also their lack of communication as a result of doing so.